Boron in wound healing: a comprehensive investigation of its diverse mechanisms - Sedighi-Pirsaraei, Nasrin; Tamimi, Amirhossein; Sadeghi Khamaneh, Faraz; Dadras-Jeddi, Sana; Javaheri, Naz (Frontiers in Bioengineering and Biotechnology, 2024)
Chronic wounds present a significant clinical challenge due to their prolonged healing time and susceptibility to infection. Boron, a trace element with diverse biological functions, has emerged as a promising therapeutic agent in wound healing. This review article comprehensively investigates the mechanisms underlying the beneficial effects of boron compounds in wound healing. Boron exerts its healing properties through multiple pathways, including anti-inflammatory, antimicrobial, antioxidant, and pro-proliferative effects. Inflammation is a crucial component of the wound-healing process, and boron has been shown to modulate inflammatory responses by inhibiting pro-inflammatory cytokines and promoting the resolution of inflammation. Furthermore, boron exhibits antimicrobial activity against a wide range of pathogens commonly associated with chronic wounds, thereby reducing the risk of infection and promoting wound closure. The antioxidant properties of boron help protect cells from oxidative stress, a common feature of chronic wounds that can impair healing. Additionally, boron stimulates cell proliferation and migration, as well as essential tissue regeneration and wound closure processes. Overall, this review highlights the potential of boron as a novel therapeutic approach for treating chronic wounds, offering insights into its diverse mechanisms of action and clinical implications.